Comparison of various doses of oral cannabidiol for treating refractory epilepsy indications: a network meta-analysis - Wang, Xin; Zhu, Haiyan; Liu, Tao; Guo, Zhi; Zhao, Chenyang; He, Zhiyi; Zheng, Wenxu (Frontiers in Neurology, 2024)
Aim To evaluate the comparative efficacy and safety of various doses of oral cannabidiol (CBD) in treating refractory epilepsy indications, thus providing more informative evidence for clinical decision-making. Methods A literature search of PubMed, Embase, the Cochrane library, and Web of Science (WoS) was performed to retrieve relevant randomized controlled trials (RCTs) that compared different doses of oral CBD with placebo or each other in refractory epilepsy indications. The search was limited from the inception of each database to January 3, 2023. Relative risk [RR] with a 95% confidence interval [CI] was used to express results. STATA/SE 14 was employed for network meta-analysis. Results Six RCTs involving 972 patients were included in the final data analysis. Network meta-analysis showed that, CBD10 (10 mg/kg/day) (RR: 1.77, 95%CI: 1.28 to 2.44), CBD20 (20 mg/kg/day) (RR: 1.91, 95%CI: 1.49 to 2.46), CBD25 (25 mg/kg/day) (RR: 1.61, 95%CI: 0.96 to 2.70), and CBD50 (50 mg/kg/day) (RR: 1.78, 95%CI: 1.07 to 2.94) were associated with higher antiseizure efficacy although the pooled result for CBD25 was only close to significant. In addition, in terms of the risk of treatment-emergent adverse events (TEAEs), the difference between different doses is not significant. However, CBD20 ranked first in terms of antiseizure efficacy, followed by CBD50, CBD10, and CBD25. For TEAEs, CBD25 ranked first, followed by CBD10, CBD50, CBD5, and CBD20. Conclusion For refractory indications, CBD20 may be optimal option for antiseizure efficacy; however, CBD25 may be best for TEAEs. Therefore, an appropriate dose of oral CBD should be selected based on the actual situation. Due to the limitations of eligible studies and the limited sample size, more studies are needed in the future to validate our findings.